Participation of Small-Scale Fishermen in the Design of a Project for Creating Artificial Reefs in the South of Brazil - José Milton Andriguetto-Filho; Naina Pierri (CUHSO)
Since 2004, a project has been in progress off the coast of ParanáState (Brazil) to set up artificial reefs and anti-trawling units on the shallowcontinental shelf. The object is to restrict large-scale bottom trawling inorder to protect and recover marine biodiversity and fish stocks, thus favouringthe sustainability of small-scale fishing. In 2005, the authors wereinvited to carry out a public participation process for the fishermen directlyaffected. The method consisted in organising four municipal discussion forums,plus a final joint meeting. Each event was preceded by intense publicity,and various communication and information techniques were used.Starting from an initial proposal for the location of the structures, and a presentationon the advantages and disadvantages of intervention, the first objectivewas to allow the fishermen to accept or reject the proposal. If it wasaccepted, the next decision was to fix the details of the spatial distributionof the structures. Acceptance was widespread, except in one district whereindustrial-scale trawling is practiced. The process revealed internal conflictsin the fishermen’s society, as well as gaps in the researchers’ knowledge offisheries and the local ecology, and the possible impacts of the project, leadingto redesign. This consultation constituted an unprecedented democratic,participative process in the history of fishery management in Paraná,which has become a regional and national reference.